Numerical investigation on nonlinear dynamics of two-state quantum dot laser subject to optical injection - Jiang, Zai-Fu; Zhang, Ding-Mei; Yang, Wen-Yan (Optics communications, 2024)
Based on the cascade relaxation model of the quantum dot (QD) lasers, the nonlinear dynamics of a two-state QD laser subject to optical injection is numerically studied. The simulation results show that, for a two-state QD laser operating at the ground-state (GS) and excited-state (ES) emission simultaneously, through adjusting the injection parameters, the two emission states can display the stable (S), injection locking (IL), suppression (SP), period-one (P1), period-two (P2), multi-period (MP), and chaotic pulse (CP) states when the frequency of the injection light is close to the GS lasing frequency. Further mapping of these dynamic states in the parameter space of frequency detuning and injection strength, it is found that the complex dynamic behaviors are mainly distributed in the negative frequency detuning region. In addition, the complexity of the chaotic signal is qualified by the permutation entropy (PE) calculating, and the high complexity signal with PE value over 0.95 is obtained. Moreover, within a certain frequency detuning range, the ES emission can be effectively suppressed by increasing the injection strength.